Focus and Challenge of National Applied Information Systems in Production Processes or Academy and Accounting Firms - Krstev, Aleksandar; Krstev, Boris; Dimitrovski, Darko; Krstev, Dejan (Natural Resources and Technology, 2013)
In this paper, focus and challenge of information systems and technologiesin production processes or academic and accounting fi rms will be shown. Inmodern conditions the successful implementation of goals and objectives ofthe enterprise or society depends on its effective use of information resources.Information resources are the basis for activities of enterprises and othersubjects in EU, the availability of information resources and opportunities andimplementation of information innovation, streamline information fl ows ofthe company, different fi rms and effective information interaction with marketplayers as Bulgaria, Ukraine, Macedonia, Serbia, Croatia, etc.